THE IMPORTANCE OF INTER-AGENCY COLLABORATION AND FAMILY LAW NETWORKING IN HANDLING FAMILY CASES: EXAMPLE FROM AUSTRALIA - Mohd Arshad, ‘Ain Husna (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2024)
Family law is one of the areas that requires collaboration of experts and practitioners from various discipline. The objective of this paper is to discuss the importance of inter-agency collaboration between various agencies in order to resolve family cases holistically. This is rooted from the understanding that family cases normally involve legal and non-legal issues that require resolutions which are beyond black and white of the law. Some cases involve financial, health or other social issues that call for advice from experts in that area. Based on the study conducted, it is found that inter-agency collaboration is needed due to limitations in the substantive family law, it is also to help vulnerable groups, and to provide holistic resolution of family disputes. Understanding the importance of such collaboration, this paper subsequently looks for example based on the practice of Australia that has established a network to coordinate family law system. The network has been able to disseminate information and conduct trainings, expedite the process of referral effectively, and establish linkages between specialists in family law. Such networking and collaboration can help the litigants dealing with their legal, emotional and practical aspect of the issues that they are facing. It also helps the agencies gain mutual understanding of each other’s role and functions. In addition to that, it may help the disputing parties making an informed decision and prepare for future adjustment to carry on with their parental obligations.